2020
DOI: 10.1371/journal.pone.0216017
|View full text |Cite
|
Sign up to set email alerts
|

Number of days required to estimate physical activity constructs objectively measured in different age groups: Findings from three Brazilian (Pelotas) population-based birth cohorts

Abstract: The present study aims to estimate the minimum number of accelerometer measurement days needed to estimate habitual physical activity (PA) among 6-(2010), 18-(2011) and 30-(2012) year-old participants, belonging to three population-based Brazilian birth cohorts. Method PA was assessed by triaxial wrist-worn GENEActiv accelerometers and the present analysis is restricted to participants with at least 6 consecutive days of measurement. Accelerometer raw data were analyzed with R-package GGIR. Description of PA m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 37 publications
0
42
1
Order By: Relevance
“…The day cycle was determined using the "from waking up to waking up the next day" approach, which means that a full night of sleep is included in a day cycle and that the duration of a day cycle may vary. Participants were excluded if they had fewer than three weekdays and one weekend day of valid wear (defined as ≥ 16 h per day), or if wear data for each 15-min period in the 24-h cycle were not available [34].…”
Section: Physical Activity and Sleepmentioning
confidence: 99%
“…The day cycle was determined using the "from waking up to waking up the next day" approach, which means that a full night of sleep is included in a day cycle and that the duration of a day cycle may vary. Participants were excluded if they had fewer than three weekdays and one weekend day of valid wear (defined as ≥ 16 h per day), or if wear data for each 15-min period in the 24-h cycle were not available [34].…”
Section: Physical Activity and Sleepmentioning
confidence: 99%
“…Participants who met the inclusion criteria for average daily MVPA were included in any analyses for which they had sufficient data (�2 days) [17]. As the criteria for deriving average daily MVPA did not require both weekend and weekdays of valid data [33], participant numbers varied by outcome.…”
Section: Accelerometer-assessed Outcomes (Including Primary Outcome)mentioning
confidence: 99%
“…It can also be speculated whether a two-week period is truly representative of a person's average activity level. However, earlier studies have indicated that monitoring of three to 7 days provides reliable estimates of PA behavior [42,[46][47][48][49]. Furthermore, an individual's level of PA is assumed to be quite a stabile trait, meaning that the individuals who were physically active at the time of the study will presumably stay active during other periods of life [50].…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar MR images of the included participants were obtained by the staff of the department of radiology, Oulu University Hospital, using 1.5-T MRI (Signa HDxt, General Electric, Milwaukee, WI) in 2012-2014 (participants aged [46][47][48]. The imaging was performed by T2weighted fast-recovery fast spin-echo (frFSE) images in the sagittal (repetition time/effective echo time (TR/ effTE) 3500/112 ms, 4 averages, field-of-view (FOV) 280 × 280 mm, acquisition matrix 448 × 224, slice thickness 3 mm with 1 mm interslice gap) and transverse planes (TR/effTE 3600/118 ms, 4 averages, FOV 180 × 180 mm, acquisition matrix 256 × 224, slice thickness 4 mm with 1 mm interslice gap) and T1-weighed fluidattenuated inversion recovery sequence images in the sagittal plane (TR/effTE 860/20 ms, inversion time (TI) of 1969 ms, 1.5 averages, FOV 280 × 280 mm, acquisition matrix 256 × 224, slice thickness 3 mm, interslice gap 4 mm).…”
Section: Determination Of MC From Lumbar Mrimentioning
confidence: 99%